(untitled) (Boston, 2009)
Offers a decision maker's perspective to emphasize the professional judgment and critical thinking skills required of accountants. This book features a textbook website that provides students a variety of electronic learning resources, including iPod content. It also integrates all the FASB Standards.
Keywords: Accounting,Kế toán